RISK BEHAVIORS IN THE TRAFFIC AMONG ACADEMIC STUDENT IN PONTA GROSSA-PR, 2005 - Caroliny Stocco; Maysa de Lima Leite; Valéria Beatris Labiak; Jorim Sousa das Virgens Filho (Universidade Federal do Paraná, 2007)
The high incidence of traffic accidents (TAs) involving young people has been attributed to proper behaviors at theirage. Thus, the present study objectified to associate risk behaviors in the traffic to demographic characteristics and the involvement inTAs among academic students of the Health area at Ponta Grossa State University - Paraná State in 2005.Aself-answerable questionnairewas used, whose studied variables were: demographic characteristics, risk behaviors in the traffic and involvement in TAs as drivers.The total sample took up 624 academics, having been excluded 126 that didn't drive.Association tests of the chi-square and odds ratiowere applied, with significant level of 5%. For the studied risk behaviors, males and the age group ranging 20 to 21 years presented alarger frequency of such behaviors. The association between the risk behaviors and the involvement in accidents revealed dependenceamong the variables